2001
DOI: 10.1046/j.1365-2958.2001.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Pho regulon negatively regulates biofilm formation by Pseudomonas aureofaciens PA147‐2

Abstract: SummaryWe report the isolation of insertional mutations to the pstC and pstA genes of the phosphate-specific transport ( pst ) operon that results in loss of biofilm formation by Pseudomonas aureofaciens PA147-2. Consistent with the known roles of the Pst system in Escherichia coli and Pseudomonas aeruginosa, both P. aureofaciens pst mutants were demonstrated to have defects in inorganic phosphate (P i ) transport and repression of Pho regulon expression. Subsequently, biofilm formation by the wild type was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 37 publications
5
81
1
3
Order By: Relevance
“…Since it has been shown that biofilm formation plays a role in early P. mirabilis UTIs and that gene products of the pst operon negatively regulate biofilm formation (Monds et al, 2001), quantitative biofilm microtitre assays were performed. After 48 h of static growth in pooled human urine, a 2.5-and eightfold reduction in biofilm formation between the HI4320 wild-type and the DpstA and DpstS mutants, respectively, was observed [wild-type, 1.65610 7 c.f.u.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since it has been shown that biofilm formation plays a role in early P. mirabilis UTIs and that gene products of the pst operon negatively regulate biofilm formation (Monds et al, 2001), quantitative biofilm microtitre assays were performed. After 48 h of static growth in pooled human urine, a 2.5-and eightfold reduction in biofilm formation between the HI4320 wild-type and the DpstA and DpstS mutants, respectively, was observed [wild-type, 1.65610 7 c.f.u.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using null mutants in pstC and pstA genes have revealed that the Pst system negatively regulates biofilm formation in Pseudomonas aureofaciens PA147-2 (Monds et al, 2001). Since biofilm formation is critical for the establishment of P. mirabilis in the human host, mutations in the Pst system may explain Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations